Isolation by genomic subtraction of DNA probes specific for Erwinia carotovora subsp. atroseptica. - Darrasse, A (1994)
Erwinia carotovora subsp. atroseptica is a pathogen of potatoes in Europe because of its ability to induce blackleg symptoms early in the growing season. However, E. carotovora subsp. carotovora is not able to produce such severe symptoms under the same conditions. On the basis of the technique described by Straus and Ausubel (Proc. Natl. Acad. Sci. USA 87:1889-1893, 1990), we isolated DNA sequences of E. carotovora subsp. atroseptica 86.20 that were absent from the genomic DNA of E. carotovora subsp. carotovora CH26. Six DNA fragments ranging from ca. 180 to 400 bp were isolated, cloned, and sequenced. Each fragment was further hybridized with 130 microorganisms including 87 E. carotovora strains. One probe was specific for typical E. carotovora subsp. atroseptica strains, two probes hybridized with all E. carotovora subsp. atroseptica strains and with a few E. carotovora subsp. carotovora strains, and two probes recognized only a subset of E. carotovora subsp. atroseptica strains. The last probe was absent from the genomic DNA of E. carotovora subsp. carotovora CH26 but was present in the genomes of many strains, including those of other species and genera. This probe is homologous to the putP gene of Escherichia coli, which encodes a proline carrier. Further use of the probes is discussed.